Perancangan Magazine Motor Custom di Kota Padang - Rahmanditto Yusardi, Yusardi; M.Nasrul Kamal (Universitas Negeri Padang, 2021)
Custom motorcycle was born to adapt to a builder and owner's will on character, shape, idea, and imagination. The custom culture is a primary part of a custom motorcycle. Printed media such as magazine plays an active role in developing custom culture in Padang. Magazine becomes a source of information capturing history on years and objects which are used as content. This magazine contains specifications and descriptions from some custom motorcycle's owners. With macro and micro photography techniques, the information is expected to be easily understood. The purpose of this design is to provide information regarding custom motorcycles with people interested in the custom motorcycle scheme as the target audience. The method of this design is Four-D method: define, design, development, disseminate. The method of analysis is 5W+1H (what, where, who, when, why, and how). The main medium in this design is magazine, simply arranged so it is easy to understand, and supported by media such as t-shirt, headband, tote bag, keychain, sketchbook, sticker, and Instagram feed so the information of this design is right on target.Keywords: Custom Motorcyle, Magazine.